CREATING A POTENTIAL PROGNOSTIC IMAGING FEATURE FOR AFTER SURGERY SURVIVAL OF SOLITARY HCC PATIENTS BY RADIOMICS SCORE - Turgunov B.Sh; Khudoykulova M.N; Turakulov U.N (Scholar Express Journals, 2024)
In this study, we aimed at developing a rad-score derived from the preoperative CECT of solitary HCC patients, based on the assumption that such rad-score may help to identify patients who were at high risk of postoperative recurrence and death and improve clinical decision making for solitary HCC patients
Keywords: HCC patients; developing; derived